Catfishing Phenomenon in the Perspective of Online Dating Services Users - Uyung Pramudiarja; Dian Artika; Dhea Hanna Prabawati (Lingkar Studi Komunikasi (LISKI), 2023)
The presence of online dating in the current digital era makes it easy for users to find their desired potential partner. The problem arises when not all online dating services require users to verify identity. Some users easily fake their identities to make them appear more attractive, known as catfishing behaviour. On the one hand, constructing an identity for a specific purpose is common in online dating services. But on the other hand, it can trigger a psychological impact for potential partners whose expectations are not met, and can even open a loophole for crime. This study wants to see the perception of online dating service users towards the catfishing phenomenon. Using the phenomenological method, this descriptive qualitative research was conducted with in-depth interviews with four informants who use online dating services with varying intensity of use and level of experience. As a result, the informants perceive a natural tendency to construct attractive impressions in online dating services. However, identity discrepancies in online dating services are at some point an unacceptable form of dishonesty. The informants also have their own anticipatory steps to avoid the snares of catfishing, from inviting video calls to doing their own profiling on social media. Keywords: Catfish, Identity, New Media, Online Dating